Investigating the Impacts of Nonuniform Proppant Distribution and Fracture Closure on Well Performance in Shale Gas Reservoirs - Zhang, Qiang; Yan, Xia; Wang, Xiaoyu; Feng, Gaocheng; Yao, Weiying; Yin, Yanjun; Zhang, Kai (Frontiers in Earth Science, 2022)
The nonuniform distribution of proppant in hydraulic fractures is an essential factor determining the accuracy of well performance evaluation in shale gas reservoirs. In particular, unpropped and propped parts hold distinct closure behavior. To study the impacts of distinct closure behavior between unpropped and propped parts in fracture on gas production, we combine the proppant transport simulation and the 3D hydro-mechanical coupling simulation. This study quantitatively indicate the significant effects of nonuniform proppant distribution and fracture closure on well performance in shale gas reservoirs. By comparing the well performances with three kinds of typical proppant distribution at the same injection volume, the distribution accumulating near the wellbore is recommended as it can reduce the impact of unpropped fracture and exploit more gas. In addition, the cases with higher natural fracture permeability are found to have less difference in the well performance with different proppant coverages. Therefore, the impacts of nonuniform proppant distribution and fracture closure on well performance in shale gas reservoirs should be investigated comprehensively.